Serum hyaluronan: A marker of liver fibrosis in patients with chronic liver disease - Tangkijvanich P. (2014)
The aim of this study was to evaluate the clinical significance of serum hyaluronan (HA) as a marker of liver fibrosis in patients with chronic liver disease. Serum HA was measured by an ELISA-based method in 28 patients with chronic hepatitis (CH), 43 patients with liver cirrhosis (LC), 57 patients with hepatocellular carcinoma (HCC) and 60 healthy controls. Mean serum HA concentration in patients with LC was 1,376.80 ± 2,568.85 ng/ml which was significantly higher than those in patients with CH, HCC and the controls (575.93 ± 732.58, and 426.36 ± 687.33, and 117.86 ± 311.11 ng/ml, respectively). Based on a ROC curve analysis, a cut-off point of 354 ng/ml discriminated between LC and other groups with a sensitivity, specificity and accuracy of 82.4%, 78.2%, and 80.2%, respectively. Mean HA concentrations were correlated with the degree of liver fibrosis, but not the grade of necroinflammatory activity. In patients with LC, the mean serum HA level was significantly increased in the Child C group (3,977.96 ± 4,906.21 ng/ml) in comparison with the Child B and A groups (1,002.63 ± 448.55, and 537.90 ± 424.16 ng/ml, respectively). We conclude that serum HA concentrations reflect the extent of liver fibrosis and severity of cirrhosis. Thus, serum HA can be a diagnostic marker of liver fibrosis and cirrhosis in patients with chronic liver disease.